The sixth form at st clare's - Cox, Pamela (Mammoth London, 2000)
New girl, Morag, detests St Clare's. She's only happy when she can escape to the local riding stables. But, now they're in the sixth form, the other girls are sad that it's their final year in their adored school. But what's wrong with Morag? Will they ever be able to understand her?